Short-term calorie restriction enhances DNA repair by non-homologous end joining in mice - Zhonghe Ke (Nature Portfolio, 2020)
Abstract Calorie restriction (CR) improves health, reduces cancer incidence and extends lifespan in multiple organisms including mice. CR was shown to enhance base excision repair and nucleotide excision repair pathways of DNA repair, however, whether CR improves repair of DNA double-strand breaks has not been examined in in vivo system. Here we utilize non-homologous end joining (NHEJ) reporter mice to show that short-term CR strongly enhances DNA repair by NHEJ, which is associated with elevated levels of DNA-PK and SIRT6.